2021
DOI: 10.3390/molecules26103003
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation of Compounds for 3CLpro Inhibitor Development on SARS-CoV-2 Variants

Abstract: COVID-19 represents a new potentially life-threatening illness caused by severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2 pathogen. In 2021, new variants of the virus with multiple key mutations have emerged, such as B.1.1.7, B.1.351, P.1 and B.1.617, and are threatening to render available vaccines or potential drugs ineffective. In this regard, we highlight 3CLpro, the main viral protease, as a valuable therapeutic target that possesses no mutations in the described pandemically relevant variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…The druggability of 3CL pro has already been demonstrated in various studies. The mutations in the dominant variants of SARS-CoV-2, such as B.1.1.7 and B.1.617, with higher transmissibility rate were studied and it has been demonstrated that most of the mutations have been found in the receptor binding domains or structural proteins, but no mutation has been reported in 3CL pro so far [38]. Therefore, 3CL pro is an attractive target for anti-COVID-19 drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The druggability of 3CL pro has already been demonstrated in various studies. The mutations in the dominant variants of SARS-CoV-2, such as B.1.1.7 and B.1.617, with higher transmissibility rate were studied and it has been demonstrated that most of the mutations have been found in the receptor binding domains or structural proteins, but no mutation has been reported in 3CL pro so far [38]. Therefore, 3CL pro is an attractive target for anti-COVID-19 drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure on the scientific community to develop a vaccine or drug has never been greater [ 81 ]. Several SARS-CoV-2 proteins have emerged as potential therapeutic targets for drug development, for example, S-protein and the viral proteases 3CL pro and PL pro [ 25 , 82 , 83 , 84 , 85 ]. With the new potential SARS-CoV-2 targets in mind, we decided to evaluate the commercially available SARS-CoV-2-targeted libraries.…”
Section: Examples Of Commercial Targeted Librariesmentioning
confidence: 99%
“…The complex contains {tert}-butyl ∼{N}-[1-[(2∼{S})-3-cyclohexyl-1-[[(2∼{S},3∼{R})-4-(cyclopropylamino)-3-oxidanyl-4-oxidanylidene-1-[(3∼{R})-2-oxidanylidene-3,4-dihydropyrrol-3-yl]butan-2-yl]amino]-1-oxidanylidene-propan-2-yl]-2-oxidanylidene-pyridin-3-yl]carbamate (OEW), a peptide-like covalent inhibitor (MW = 585.69 g/mol). As described previously ( Jukič et al, 2021 ), this complex comprises the peptidomimetic inhibitor OEW, which occupies all major pockets at the active site of the enzyme, leaving the S1 pocket accessible and the enzyme in the active conformation. After superposition with a reference structure (PDB ID:6LU7), the catalytic binding pocket was defined around Cys145 ( Jin et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…, a peptide-like covalent inhibitor (MW 585.69 g/mol). As described previously (Jukič et al, 2021), this complex comprises the peptidomimetic inhibitor OEW, which occupies all major pockets at the active site of the enzyme, leaving the S1 pocket accessible and the enzyme in the active conformation. After superposition with a reference structure (PDB ID:6LU7), the catalytic binding pocket was defined around Cys145 (Jin et al, 2020).…”
Section: Target Preparationmentioning
confidence: 99%